The effects of Co addition on the mechanical and microstructural properties of the matrix material of a Fe-based marble cutting tool - Budak, S.; Kaplan, M. (Redakcia Kovove Materialy, 2016)
In this study, four different kinds of marble cutting matrices with a base composition of Fe-Cu-Sn and with variable amounts of Co powder were produced. For compaction, hot sintering process was carried out at 850 degrees C under 35 MPa for 4 min. The mechanical and microstructural properties of the matrix materials were determined using SEM with EDS, three-point bending test, density and hardness measurement techniques. The addition of Co powders to the matrix and the subsequent hot sintering process affected the mechanical and microstructural properties of the cutting tool, such as hardness, total elongation, % porosity and phase distribution.
Keywords: marble cutting tools; cutting matrix material; hot sintering process; mechanical and microstructural properties